Acquisition learning is stronger for aversive than appetitive events - van der Schaaf, ME; Schmidt, K; Kaur, J; Gamer, M; Wiech, K; Forkmann, K; Bingel, U (Springer Nature, 2022)
Appetitive and aversive learning are both key building blocks of adaptive behavior, yet knowledge regarding their differences is sparse. Using a capsaicin heat pain model in 36 healthy participants, this study directly compared the acquisition and extinction of conditioned stimuli (CS) predicting pain exacerbation and relief. Valence ratings show stronger acquisition during aversive compared to appetitive learning, but no differences in extinction. Skin conductance responses and contingency ratings confirmed these results. Findings were unrelated to individual differences in pain sensitivity or psychological factors. Our results support the notion of an evolutionarily hardwired preponderance to acquire aversive rather than appetitive cues as is protective for acute aversive states such as pain but may contribute to the development and maintenance of clinical conditions such as chronic pain, depression or anxiety disorders.